Mengembangkan Kemampuan Membilang Pada Anak Usia 5-6 Tahun Melalui Metode Permainan Dadu di Paud Dian - Miswardah, Siti; Awal Maulana, Redi; Elnawati, Elnawati (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
This research aims to develop counting skills in children aged 5-6 years through the dice game method at PAUD Dian. Early Childhood Education (ECE) plays a crucial role in preparing children for further education, especially in cognitive development which includes counting abilities. The play-based learning method is expected to enhance children's interest and participation in learning activities. Initial observations revealed that many children were disinterested and not proficient in counting. Therefore, this study utilized dice games as an engaging learning medium. The results indicate that this method is effective in improving children's counting skills and provides benefits for teachers, students, and educational institutions.